The computer says no. (Economist, 2008)
The article reports on the development of image-processing software that would enhance the ability of computers to analyze the composition of digital images. Research into the matter conducted by James Wang of Pennsylvania State University is described. The creation of this technology would have a number of applications including the detection of art forgeries.